2016
DOI: 10.1163/15707563-00002498
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in food intake, thermogenesis and body mass in the tree shrew (Tupaia belangeri) is affected by food restriction and refeeding

Abstract: Physiological adjustments are important strategies for small mammals in response to variation in food availability. To determine the physiological mechanisms affected by food restriction and refeeding, tree shrews were restricted to 85% of initial food intake for 4 weeks and refedad libitumfor another 4 weeks. Changes in food intake, body mass, thermogenesis, body composition, mitochondrial cytochromecoxidase activity, uncoupling protein-1 content in brown adipose tissue and serum leptin levels were measured. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Second, the physiology and ecology of tree shrews have changed, and the skull and molars exhibited differentiation during northward migration; for example, the resting metabolic rate of T. belangeri in its northernmost distribution was significantly higher than that of Urogale and Ptilocercus lowii in its southernmost distribution (Jia et al 2009;Zhu et al 2013). Moreover, T. belangeri has shown adaptation characteristics to cold that are common for small northern mammals (Zhang et al 2012;Zhu et al 2012;Gao et al 2016). Finally, on the basis of population history, cold temperatures may affect the T. belangeri population size, as the effective population size historically decreased during cold periods, especially during the last glacial period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the physiology and ecology of tree shrews have changed, and the skull and molars exhibited differentiation during northward migration; for example, the resting metabolic rate of T. belangeri in its northernmost distribution was significantly higher than that of Urogale and Ptilocercus lowii in its southernmost distribution (Jia et al 2009;Zhu et al 2013). Moreover, T. belangeri has shown adaptation characteristics to cold that are common for small northern mammals (Zhang et al 2012;Zhu et al 2012;Gao et al 2016). Finally, on the basis of population history, cold temperatures may affect the T. belangeri population size, as the effective population size historically decreased during cold periods, especially during the last glacial period.…”
Section: Discussionmentioning
confidence: 99%
“…Tupaia belangeri is widely distributed throughout Yunnan, Guizhou, Sichuan, Guangxi, and Hainan island of China. It is a unique species of Scandentia in China (Gao et al 2016(Gao et al , 2017 and is an interesting species for studying adaptation to diverse environments (Zhu et al 2014;Wang et al 2015), as its natural distribution covers a large variety of environments, ranging from tropical to subtropical and from plains to mountainous areas (Sargis et al 2016). There has been extensive dispute about the subspecies classification of T. belangeri in China.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that tree shrews show seasonal thermogenesis (Zhu et al 2012) and have a higher resting metabolic rate (RMR) in their thermoneutral zone (TNZ) than other small mammals (Wang et al 1994; Xiao et al 2010). This may be associated with food resource and quality, as fasting and FR has been demonstrated to significantly decrease metabolic thermogenesis (Gao et al 2014, 2016). Food supply may thus have influenced the evolution of metabolic plasticity in tree shrews.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that tree shrews show seasonal thermogenesis (Zhu et al 2012) and have a higher resting metabolic rate (RMR) in their thermoneutral zone (TNZ) than other small mammals (Wang et al 1994;Xiao et al 2010). This may be associated with food resource and quality, as fasting and FR has been demonstrated to significantly decrease metabolic thermogenesis (Gao et al 2014(Gao et al , 2016. Food supply may thus have influenced the evolution of metabolic plasticity in tree shrews.…”
mentioning
confidence: 99%